Spinal drug delivery: technology, biology and toxicology - Yaksh, Tony (Henry Stewart Talks, 2009)
Pain: concepts and early anatomy, Role of sensory nerves and spinal cord, Enabling technology for spinal anesthesia, Rapid evolution of spinal anesthetic delivery in the US, Early appreciation of risks of spinal anesthesia, Modulation of spinal processing, Targeting drugs at spinal function, Other systems which regulate spinal afferent transmission, Pain selectively diminished by spinal opioids, Spinal mu/delta opioid action, Spinal analgesics: animal and human pain, Safety of spinal drugs, Early safety issues with spinal anesthetic, Classes of spinal toxicity, Intrathecal lidocaine and toxicity, Spinal toxicity: root, parenchyma, meningeal, Human intrathecal morphine: granuloma, IT morphine and granulomas concentration vs. dose, Future and neuraxial drug delivery